2007
DOI: 10.1186/1742-4690-4-83
|View full text |Cite
|
Sign up to set email alerts
|

Antibody microarray analysis of cell surface antigens on CD4+ and CD8+ T cells from HIV+ individuals correlates with disease stages

Abstract: Our study not only confirmed cell surface antigens previously reported to be related to HIV disease stages, but also identified 5 novel ones. Of these five, three markers point to major changes in responsiveness to certain cytokines, which are involved in Th1 responses. For the first time our study shows how density of cell surface antigens could be efficiently exploited in an array manner in relation to HIV disease stages. This new platform of identifying disease markers can be further extended to study other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…This study, together with our study on cell surface antigens using a protein microarray (8), has demonstrated that the CD8 ϩ T-cell transcriptome and its surface are more informative in differentiating HIV disease groups than the CD4 ϩ T cells. This is consistent with our recent findings, which showed that the whole-genome transcriptome in primary CD8…”
mentioning
confidence: 62%
“…This study, together with our study on cell surface antigens using a protein microarray (8), has demonstrated that the CD8 ϩ T-cell transcriptome and its surface are more informative in differentiating HIV disease groups than the CD4 ϩ T cells. This is consistent with our recent findings, which showed that the whole-genome transcriptome in primary CD8…”
mentioning
confidence: 62%
“…In an antibody microarray analysis of 135 T-cell surface antigens, Wu et al (2007) showed that LTNP CD4 + T cells had an upregulated cell-surface expression of HLA-DR, CD71 and CD38 compared with viraemic patients on highly active antiretroviral therapy (HAART).…”
Section: Some Evidence Suggests That Ltnps Have Reduced Cd4mentioning
confidence: 99%
“…The antiinflammatory IL-4 secretion probably provided some advantages to virus survival in progressor CD4 + T cells. Additionally, Wu et al (2007) used antibody microarrays to show that LTNP, but not progressor CD8 + T cells, had upregulated CD16 and CD56 cell surface expression, which activated NK cells.…”
Section: Cd8mentioning
confidence: 99%
“…Cytokine antibody arrays have been successfully used with many different biological sample sources, including serum [80][81][82][83], urine [84][85][86], plasma [87,88], bronchoalveolar lavage [89], gingival crevicular fluid [90], synovial fibroblast supernatants [91], CSF [92], sputum [93]; [94], tears [95], laser capture-microdissected tissue [96], cell lysates [97], tissue lysates [98], conditioned medium [99], liver cyst fluids [100], saliva [101], breast interstitial fluid [102] and many others.…”
Section: Application Of Cytokine Antibody Arrays In Biomarker Discovementioning
confidence: 99%